Regulating Subcellular Metal Homeostasis: The Key to Crop Improvement - Bashir, Khurram; Rasheed, Sultana; Kobayashi, Takanori; Seki, Motoaki; Nishizawa, Naoko K. (Frontiers in Plant Science, 2016)
Iron (Fe), zinc (Zn) manganese (Mn), and copper (Cu) are essential micronutrient mineral elements for living organisms, as they regulate essential cellular processes, such as chlorophyll synthesis and photosynthesis (Fe, Cu, and Mn), respiration (Fe and Cu), and transcription (Zn). The storage and distribution of these minerals in various cellular organelles is strictly regulated to ensure optimal metabolic rates. Alteration of the balance in uptake, distribution, and/or storage of these minerals severely impairs cellular metabolism and significantly affects plant growth and development. Thus, any change in the metal profile of a cellular compartment significantly affects metabolism. Different subcellular compartments are suggested to be linked through complex retrograde signaling networks to regulate cellular metal homeostasis. Various genes regulating cellular and subcellular metal distribution have been identified and characterized. Understanding the role of these transporters is extremely important to elaborate the signaling between various subcellular compartments. Moreover, modulation of the proteins involved in cellular metal homeostasis may help in the regulation of metabolism, adaptability to a diverse range of environmental conditions, and biofortification. Here, we review progress in the understanding of different subcellular metal transport components in plants and discuss the prospects of regulating cellular metabolism and strategies to develop biofortified crop plants.